Microstructure and Ferroelectric Properties of Direct-Patternable Bi3.25La0.75Ti3O12 Films Prepared by Photochemical Metal-Organic Deposition - Park, Hyeong-Ho; Kim, Hyuncheol; Wang, Seok-Joo; Park, Hyung-Ho; Kim, Tae Song; Hill, Ross H. (TAYLOR & FRANCIS LTD, 2009)
The microstructure and ferroelectric properties of Bi3.25La0.75Ti3O12 films prepared by photochemical metal-organic deposition using photosensitive precursors were characterized. The diffraction intensities showed a distribution similar to Bi3.25La0.75Ti3O12 ceramics, and Pt(111) was found to not influence the growth orientation of Bi3.25La0.75Ti3O12 films. The values of measured remnant polarization and dielectric constant of Bi3.25La0.75Ti3O12 films annealed at 650 and 700 degrees C were 8.7, 16.0 mu C/cm(2) and 172, 276, respectively. The films remained free of fatigue up to 10(9) switching cycles. These results suggest the possible application of ferroelectric Bi3.25La0.75Ti3O12 film, relatively easily and without high cost process such as dry etching.
Keywords: INDUCTIVELY-COUPLED PLASMA; TITANATE THIN-FILMS; ELECTRICAL-PROPERTIES; CRYSTALLIZATION; ORIENTATION; BI4TI3O12